Analisis Strategi Pemasaran untuk Meningkatkan Penjualan Produk Box Panel - Galih Alfikry; Dimas Arya Saputra (RESWARA: Jurnal Riset Ilmu Teknik, 2023)
The increasingly competitive industrial market requires companies to implement effective marketing strategies to enhance product sales performance. Box panel products, which play a crucial role in electrical and industrial infrastructure, face challenges related to market penetration, price competition, and limited promotional strategies. This study aims to analyze appropriate marketing strategies to increase box panel product sales by integrating various strategic marketing frameworks. The research adopts a qualitative descriptive approach using literature-based analysis supported by strategic marketing tools such as SWOT analysis, marketing mix (4P), and strategic prioritization models. Data were obtained through secondary sources, including relevant scientific journals and empirical studies on marketing strategy implementation in manufacturing and industrial sectors. The findings indicate that product quality differentiation, competitive pricing strategies, expanded distribution channels, and intensified promotional efforts—particularly through digital marketing—significantly influence sales growth. Furthermore, the integration of internal strengths and external opportunities enables companies to formulate adaptive and sustainable marketing strategies. This study concludes that a comprehensive and structured marketing strategy is essential to improving box panel sales performance and maintaining competitiveness in the industrial market. The results provide practical implications for industrial companies and contribute to the development of strategic marketing literature in the manufacturing sector.